Construction Services Income Tax Analysis - Subhan Subhan (Advances in Taxation Research, 2023)
This study aims to determine the calculation, deduction, deposit, and reporting of income tax article 4 paragraph 2 for construction services at Nindya-Passokorang (KSO). The value of the budget contract uses funds sourced from WINRIP IBRD LOAN NO. 8043 - ID of Rp. 202,911,052,727. The data analysis method used is descriptive quantitative analysis of research results using numerical calculations to obtain data, the data source used in this study is primary data in the form of subject data obtained directly from the source and secondary data regarding the general description of service companies. construction. The results show that the income tax rate of article 4 paragraph 2 using a 3% rate with the qualifications of large and medium enterprises Nindya-Passokorang (KSO) no longer pays the final income tax article 4 paragraph 2 because service users are tax cutters. Based on research conducted in terms of monthly tax reporting that has been routinely carried out in order to avoid the applicable tax penalties.